REPORT OF THE TENTH COORDINATION AND EVALUATION MEETING OF THE PAN-AFRICAN CAMPAIGN AGAINST BOVINE RINDERPEST AND CONTAGIOUS PLEUROPNEUMONIA (P.A.R.C) - African Union Inter-African Bureau for Animal Resources; AU-IBAR (My University, 2021)
The opening ceremony of the Meeting was presided over by His Excellency Mr. Alassane Dialy N'DIAYE, Minister in charge of Fisheries and Maritime Transport, substituting for Mr Robert SAGNA, State Minister, Minister of Agriculture of Senegal in the presence of Mr Andre VANHAEVERBEKE, Chief Delegate of the European Commission, of the Representative of the United Nations Food and Agriculture Organization (FAO) in Senegal and Mr. Mouhamadou Moustapha MBENGUE, Director of Cabinet of the State Minister, Minister of Agriculture Three speeches were made during the opening ceremony. Taking first the floor, Dr. MASIGA, OAU/IBAR Director thanked Senegal for hosting this 10th Meeting and for the warm hospitality extended to each delegate. He also thanked the European Union for its support to the PARC Project. The main objective of the PARC Project which is the eradication of Bovine Rinderpest has been reached because for almost 8 years, no outbreak has been reported in West and Central Africa. Consequently, it is necessary that the countries involved be declared provisionally free from this disease following the procedures of the International Office of Epizootic Diseases (OIE). The current meeting will provide an opportunity to discuss this matter and make a recommendation. He concluded his speech by stressing the importance of the Privatization of the Veterinary Profession. Following the OAU/IBAR Director, the Chief Delegate of the European Commission in Senegal, Mr. Andre VANHAEVERBEKE, expressed satisfaction over the results obtained by the PARC Project which represents on the side of the Onchocerciasis Program an example of success in Africa. Since the agreement reached between the Organization of African Unity and the European Union in 1986, about 70 billion CFA Francs have been mobilized for the funding of the PARC Project. The success of this project is related on the one hand to its regional approach and, on the other hand, to the setting up of flexible procedures making possible a direct mobilization of resources at the State level. He reaffirmed the commitment of the European Union to sustain the efforts of countries for a sustainable development of African livestock. In his speech, Minister Alassane Dialy N'Diaye expressed satisfaction over the efforts made by the PARC Project in the last 10 years in the eradication of Bovine Rinderpest in African Countries. The results are judged today to be very satisfactory because no outbreak of the disease has been reported in West and Central Africa since 1988; this makes it possible to plan a common strategy to let countries declare themselves in the short run free from Rinderpest. 2 He also expressed satisfaction over the fact that this 10th Meeting discuss other important topics such as control of CBPP and the State of Progress of the Privatization of the Veterinary Profession. The Minister then thanked the European Union for its constant commitment to African livestock, as well as FAO for its technical support. Finally he concluded his speech by congratulating the OAU/IBAR, the Regional Coordination and all the National Coordinations for the brilliant results obtained. The session was suspended after this ceremony before resumption of the proceedings of the meeting with the setting up of the bureau composed as follows: Chairman Senegal Vice-Chairman Ghana Rapporteurs Cote-d'Ivoire and Central African Republic The PARC-SENEGAL National Coordinator was designated as resource person
Keywords: Pan-African Control of Epizootics (PACE)